PREVALENCE OF WORK RELATED LOW BACK PAIN IN PHYSICAL THERAPIST PROFESSIONAL FROM THE CITY OF TAIF, KSA (International Journal of Physiotherapy, 2016)
Background: Physical therapy often is used in the management of work-related low back pain (LBP). Little information, however, is known about work related low back pain that may occur in physical therapy experts themselves. Work related low back agony speaks to one of the real wellbeing issues that happen in well-beings experts. The point of this study is to examine the pervasiveness of work related low back pain in physical therapy experts, and its connection to the way of work.Methods: One hundred and seven physical therapy experts working at general hospitals at Taif, KSA took part in this study, their age ranged from 25 to 60 years, and they were complaining from low back pain for more than 3 months and their current pain for at least three or more weeks. Every subject was requested to finish the Oswestry Low Back Pain Disability Index Questionnaires that comprised of 15 close-ended inquiries.Results: We analyzed Data by utilizing descriptive statistics to gauge the predominance of low back pain in physical therapy experts and to explore connection between back pain and hospital facility work. Out of two hundred thirty physical therapist advisor, one hundred and ten (47.8%) physical specialists finished/gave back the surveys. three polls were rejected from investigation since members had missed a few things in filling the survey. In this manner, just information from 107 members was utilized to figure the predominance rates. It was found that the commonness of work related low back pain in physical therapy expert is equivalent 72%. It was found that a connection between the works related low back pain and age, proficient rank, and specialty.Conclusion: There is a higher occurrence of work related back pain among physiotherapist expert and this may be impacted by age, proficient rank and specialty.